A taxonomic note on Erionota acroleuca (Wood-Mason & de Nicéville, 1881) stat. rest. (Lepidoptera: Hesperiidae) - Xue, Guo-Xi; Lo, Yik Fui Philip (Zootaxa, 2015)
The purpose of this paper is to restore Erionota acroleuca (Wood-Mason & de Nicéville, 1881) as a valid name, and to establish Erionota acroleuca apicalis de Jong & Treadaway, 1992 as a new subspecific combination, with its immature biology briefly introduced.